Drip irrigation video: Testimonial at Kairini Farm of Chuka University - Kimani, Owen Samuel (2022)
A video clip showcasing the irrigation potential for production in dryland agro-ecologies facilitated by Alliance-CIAT through AICCRA Kenya - a project of the World Bank. The clip is part of AICCRA Kenya's capacity-building, networking, and partnership scaling efforts with Universities.